The genus Pseudohemiodon (Siluriformes, Loricariidae) in Ecuador, with the description of a new species - Provenzano-Rizzi, Francisco; Argüello, Pablo; Barriga-Salazar, Ramiro (Zootaxa, 2022)
At the Fish Collection of the Museo de la Escuela Politecnica Nacional (MEPN), Quito, the specimens of the genus Pseudohemiodon were revised and three species were identified. The three species inhabit the Amazon versant of Ecuador. Chronologically the species are: P. lamina (Günther 1868) originally described from Xeberos (Jeberos), Peru; P. apithanos Isbrücker & Nijssen 1978, originally described from the Conejo River, Putumayo River system, Ecuador, and a new species described herein. The new species was caught in the Aguarico River, Napo River system, and is represented by two small sized specimens. It is distinguished from all congeners by the combination of the following characters: abdomen totally covered with small to medium-sized, irregularly shaped plates; absence of small plates, anterior to gill openings; eyes relatively small, and six to seven dark transverse bands, posterior to the dorsal-fin. Isbrücker & Nijssen (1978) indicate the presence of P. laticeps (Regan 1904) in Ecuador; however we didn’t find any specimen of this species. The specimens that could potentially be identified as P. laticeps are large sized specimens of P. apithanos. Some external morphological characters, morphometric and meristic data of analyzed specimens of P. apithanos and P. lamina are provided.